The effect of working capital management on profitability : evidence from Malaysia / Linda Sim Siew Kian - Sim, Linda Siew Kian (2013)
Working capital management is part of the financial considerations that a finance manager needs to determine and plays an important role in determining the profitability of the firms. In view of its importance, this study aims to investigate on the effect of working capital management components and working capital management policy towards profitability of firms in services and manufacturing sector in Malaysia for five years period from 2006 to 2010, which also coincides with the implementation of the Ninth Malaysia Plan and Third Industrial Master Plan. Further, the objective of this study is to examine whether there is any significant difference in profitability between firms in services and manufacturing sector during the period of 2006 to 2010.